2017
DOI: 10.1177/2047487317739079
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing as prognostic indicators: Comparisons among heart failure patients with reduced, mid-range and preserved ejection fraction

Abstract: Aims We aimed to determine the differences of impact of cardiopulmonary exercise testing (CPX) parameters on prognosis of heart failure with reduced left ventricular ejection fraction (HFrEF), preserved ejection fraction (HFpEF) and mid-range ejection fraction (HFmrEF). Methods We compared clinical characteristics and CPX parameters among the three groups, and the value of each CPX parameter to predict adverse cardiac events (cardiac deaths and re-hospitalizations for heart failure), cardiac deaths and all-cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 27 publications
8
83
0
1
Order By: Relevance
“…23,24 Age and the proportion of women were the highest in the HFpEF group, followed by those in the HFmrEF and HFrEF groups; these results are comparable with reports from the USA and Europe. 23,24 Age and the proportion of women were the highest in the HFpEF group, followed by those in the HFmrEF and HFrEF groups; these results are comparable with reports from the USA and Europe.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…23,24 Age and the proportion of women were the highest in the HFpEF group, followed by those in the HFmrEF and HFrEF groups; these results are comparable with reports from the USA and Europe. 23,24 Age and the proportion of women were the highest in the HFpEF group, followed by those in the HFmrEF and HFrEF groups; these results are comparable with reports from the USA and Europe.…”
Section: Discussionsupporting
confidence: 85%
“…23,24 Age and the proportion of women were the highest in the HFpEF group, followed by those in the HFmrEF and HFrEF groups; these results are comparable with reports from the USA and Europe. 23,24 However, the Chronic Heart Failure Analysis and Registry in the Tohoku District (CHART)-2 reported that coronary artery disease was found in nearly 50% of HF patients. In general, coronary artery disease is a major type of underlying heart disease in HF patients in the USA and Europe (~50%).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…CPET and ESE provide several parameters with a well‐known prognostic value in HF individually, also when systolic function (i.e. LVEF) is preserved . The aim should be to interrupt the slippery slope towards HFpEF, which is a more complex and heterogeneous disease than HFrEF .…”
Section: Discussionmentioning
confidence: 99%
“…CPET parameters in HFmrEF patients were intermediate between heart failure with preserved ejection fraction (HFpEF) and HFrEF, probably because the pathophysiology of HFmrEF overlaps with that of both HFpEF and HFrEF. 17 …”
Section: Exercise Measurement Cardiopulmonary Exercise Testingmentioning
confidence: 99%